Children with Fetal Alcohol Syndrome are impaired at place learning but not cued-navigation in a virtual Morris water task - Hamilton, Derek A; Kodituwakku, Piyadasa; Sutherland, Robert J; Savage, Daniel D (Behavioural brain research, 2003)
We employed a computerized (virtual) Morris water task (VMWT) to measure place learning and cued-navigation in eight adolescent males (9.5–16.5 years old) diagnosed with Fetal Alcohol Syndrome (FAS). Eight adolescent males matched for age and ethnicity with no history of prenatal alcohol exposure served as controls. Participants were trained to navigate to a hidden platform in a fixed location relative to a set of four conspicuous extramaze cues. After 20 hidden platform trials, a single no-platform probe trial was conducted, followed by 8 trials during which the platform was visible (cued-navigation). The FAS group traveled further than controls to navigate to the hidden platform during training. During the probe trial, controls navigated more directly to the platform region and persisted in searching where the platform had been more than the FAS group. Cued-navigation was comparable in both groups, suggesting that group differences in place learning were not attributable to visual-motor or motivational deficits in the FAS subjects. This pattern of impaired place learning and spared cued-navigation is similar to that reported in rats exposed to ethanol during periods of prenatal or early postnatal brain growth, as well as in animals with hippocampal damage.